Enhanced Catalysis of P-doped SnO2 for the V2+/V3+ Redox Reaction in Vanadium Redox Flow Battery - Feng, Xiaojian; Zhang, Zixuan; Zhang, Tongxue; Xue, Jing; Han, Chao; Dai, Lei; Wang, Ling; He, Zhangxing (Frontiers in Chemistry, 2021)
In this work, nanosized P-doped SnO2 (SnO2-P) was prepared by a sol-gel method as a catalyst for the V3+/V2+ redox reaction in vanadium redox flow battery. Compared with SnO2, the electrochemical performance of SnO2-P is significantly improved. This is because P doping provides more active sites and shows greatly improved electrical conductivity, thereby increasing the electron transfer rate. As a result, SnO2-P shows better catalytic performance than SnO2. SnO2-P modified cell is designed and exhibits an increase of 47.2 mA h in discharge capacity and 8.7% in energy efficiency compared with pristine cell at 150 mA cm-2. These increases indicate that the modified cell has a higher electrolyte utilization rate. This study shows that SnO2-P is a new and efficient catalyst for vanadium redox flow battery.